THE PUBLIC-PRIVATE PARTNERSHIPS IN THE VOCATIONAL EDUCATION AND TRAINING SYSTEM PARADIGMS: COMPARATIVE ANALYSIS - Валентина Попова (National Academy of Educational Sciences of Ukraine, 2022)
The article identifies the factors which influence changes in the public-private partnerships (PPPs) paradigm in the system of vocational and technical education (VET) took place. The study is based on a comparative analysis of the foreign experience of implementing PPPs in the VET system. The reasons for changing the paradigm of the state dictate to the publicprivate partnerships are clarified, and the sequence of transition to the paradigm of delegating by the state to the private sector not only economic risks but also the authority to comply with public values is determined. The study revealed that the PPPs paradigm in the VET system was formed under the influence of the concept of the New Public Management, which over time transformed into the New Public Governance with an orientation to public values. The main provisions of PPPs paradigms in the VET system comparative analysis showed that changes have taken place in the status of the pupil (student) in the private partners' role and in the state responsibility sphere. The new PPPs paradigm for VET main provisions evolution consequence was changing in: the scope of declared goals, the size of investments, planning horizon, economic efficiency, the number of involved partners, and the distribution of risks between private and public partners. The results of the study confirmed that the presence of a paradigm as a model for posing a problem is mandatory for the social sciences: after all, it narrows the circle of scientific research, provides a research methodology, tools, and determines the practice of scientific knowledge. The comparative analysis showed that the modern paradigm of scientific research, that is, the model for posing a problem and solving it in the VET system, is the introduction of PPPs with a focus on public values.